Prevalence of cancer in Parkinson's disease related to R1441G and G2019S mutations in LRRK2. Issue 6 (19th December 2013) - Ruiz‐Martínez, Javier; de la Riva, Patricia; Rodríguez‐Oroz, Maria C.; Mondragón Rezola, Elisabet; Bergareche, Alberto; Gorostidi, Ana; Gago, Belen; Estanga, Ainara; Larrañaga, Nerea; Sarasqueta, Cristina; López de Munain, Adolfo; Martí Massó, José F.
ABSTRACT An inverse relationship between Parkinson's disease (PD) and cancer has been described. However, the association between cancers and genetic forms of PD, in particular the R1441G mutation in the LRRK2 gene, is not well known. The objective of this work was to analyze cancer prevalence in PD patients with R1441G or G2019S mutations in LRRK2, and in idiopathic PD (iPD). A total of 732 patients with PD (70 and 25 carriers of R1441G or G2019S mutations, respectively), and 177 controls, were linked using a population‐based cancer registry of the Spanish province of Gipuzkoa. Cancer prevalence was not significantly higher in PD‐G2019S carriers (20%) than in PD‐R1441G carriers (14.3%), iPD (13.8%), or controls (12.5%). With the exception of a high prevalence of hematological cancers (crude odds ratio of 7.1) in the R1441G group, specific cancer types were not increased in PD mutation carriers. In both the carrier and iPD groups, cancers were diagnosed after the onset of PD. PD patients had a similar prevalence of cancer to control subjects. There was no increased association between G2019S or R1441G mutations and any type of cancer. Although there was a higher prevalence of hematological cancers in the R1441G group, the low number of such cancers overall makes this finding of uncertain significance. There was a slightly higher but not statistically significant prevalence of non‐skin cancers in the G2019S group, suggesting that further study to evaluate the association should be undertaken prior to ascribing an increased cancer risk to this population. © 2013 International Parkinson and Movement Disorder Society